1969
DOI: 10.1001/archpedi.1969.02100030245024
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Hernias in Females and the Testicular Feminization Syndrome

Abstract: The purpose of this seminar is to discuss a problem which has aroused considerably difference of opinion among the staff members of this hospital. The problem is: Should every female with inguinal hernias be studied to determine if she has the testicular feminization syndrome? Recently, I received a complaint from a member of the staff about such a patient. The patient had undergone surgery and, on the day of discharge, the intern made a buccal smear for sex chromatin determination in the presence of the paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
2
6
0
1
Order By: Relevance
“…Kaplan et al estimated this incidence to be 1.4%. 12 This was our finding as well. The frequency rose to 6.3% in females with bilateral inguinal hernias and 12.5% in females with bilateral synchronous inguinal hernias.…”
supporting
confidence: 84%
“…Kaplan et al estimated this incidence to be 1.4%. 12 This was our finding as well. The frequency rose to 6.3% in females with bilateral inguinal hernias and 12.5% in females with bilateral synchronous inguinal hernias.…”
supporting
confidence: 84%
“…El tratamiento es con orquiectomía bilateral y terapia de reemplazo hormonal posterior, ya que a mayor edad se asocia un mayor riesgo de malignidad testicular 12 . El apoyo psicológico y asesoramiento también son esenciales, tanto para los pacientes como para sus familias.…”
Section: Discussionunclassified
“…Prompt diagnosis also allows for education about the risk of gonadal malignancy. Although most cases of testicular cancer in patients with CAIS do not occur until after puberty, early malignant transformation has been documented [9,11]. Some advocate leaving the gonads in situ through puberty because testosterone is converted to estrogen and aids in secondary sexual development [13].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this association, it has been suggested that all premenstrual girls with inguinal hernias should be examined for CAIS [8,9]. Unless specific steps are taken, surgeons can repair inguinal hernias and not recognize the underlying condition, missing the opportunity for early diagnosis.…”
mentioning
confidence: 99%